(untitled) (Revista Kriterion, 2020)
The purpose of this paper is to bring out, by means of a simple thought experiment involving demonstratives, a discrepancy between what is expressed and what is believed (which contradicts the Theory of Direct Reference), and to consider some consequences of this – most notably, whether we might hold, for example, that the ancients never believed that Hesperus is not Phosphorus.